Comparing the Efficacy of Concomitant Therapy with Sequential Therapy as the First-Line Therapy of Helicobacter pylori Eradication - Sung Min Jung; Dae Young Cheung; Jin Il Kim; Il Kim; Hyeonjin Seong (Gastroenterology Research and Practice)
Background. The decline of Helicobacter pylori (H. pylori) eradication rates with standard triple therapy resulted in a search for novel therapies for first-line therapy of H. pylori infection. Aim. The aim of the study is to compare the efficacy of concomitant therapy with sequential therapy as the first-line therapy of H. pylori eradication. Methods. We reviewed medical records of patients who were confirmed to have H. pylori infection and received eradication treatment from September 2012 to March 2015. The concomitant group was treated with rabeprazole, amoxicillin, clarithromycin, and metronidazole for 7 days. The sequential group was treated with rabeprazole and amoxicillin for 5 days and then rabeprazole, clarithromycin, and metronidazole for an additional 5 days. Six weeks after the treatment period, patients in both groups underwent 13C-Urea breath test (UBT) to confirm H. pylori eradication. Results. The eradication rate was 90.3% in the concomitant group and 85.5% in the sequential group. However, the eradication rates between the two groups showed no statistical difference (P=0.343). Conclusion. No statistical difference was found in eradication rates between the two groups. However, in areas where antibiotic resistance is high, concomitant therapy may be more effective than sequential therapy for H. pylori eradication.